Genetic Studies in the Sleep Disorder Narcolepsy - Kadotani, Hiroshi; Faraco, Juliette; Mignot, Emmanuel (Genome Research, 1998)
Narcolepsy is a chronic neurologic disorder characterized by excessive daytime sleepiness and abnormal manifestations of REM sleep including cataplexy, sleep paralysis, and hypnagogic hallucinations. Narcolepsy is both a significant medical problem and a unique disease model for the study of sleep. Research in human narcolepsy has led to the identification of specific HLA alleles (DQB1*0602 andDQA1*0102) that predispose to the disorder. This has suggested the possibility that narcolepsy may be an autoimmune disorder, a hypothesis that has not been confirmed to date. Genetic factors other than HLA are also likely to be involved. In a canine model of narcolepsy, the disorder is transmitted as a non-MHC single autosomal recessive trait with full penetrance (canarc-1). A tightly linked marker for canarc-1 has been identified, and positional cloning studies are under way to isolate canarc-1 from a newly developed canine genomic BAC library. The molecular cloning of this gene may lead to a better understanding of sleep mechanisms, as has been the case for circadian rhythms following the cloning of frq, per, and Clock.